Study on the Permeability of Nonmetallic Materials in the Hydrogen-Doped Pipeline - Ouyang, Xin; Ai, Hongni; Pei, Yebin; Cong, Chuanbo; Sun, Sheng; Liu, Xiaoben (E3S web of conferences, 2024)
As the most efficient way to transport large quantities of hydrogen over long distances, Hydrogendoped NG pipeline has been actively promoted and developed. Hydrogen into the pipeline will have a variety of effects, as the smallest gas molecules, hydrogen on the pipeline valve, and other key equipment nonmetallic materials have a stronger penetration than natural gas, which is bound to increase the leakage of equipment, there are huge security risks. In this paper, the permeability of non-metallic materials in hydrogendoped NG pipelines is studied by permeability experiments. Seven common non-metallic materials for natural gas pipeline valves and key equipment are compared and selected. The numerical simulation model of hydrogen permeation in non-metallic materials was established to explore the permeability of non-metallic materials under different pressures, temperatures, and mixing ratios of hydrogen. The non-metallic sealing materials suitable for the hydrogen-doped environment are optimized, which can furnish reference for the engineering promotion and technology development of hydrogen-doped natural gas pipeline transportation.